TRRUST v2: an expanded reference database of human and mouse transcriptional regulatory interactions. Issue Volume 46:Issue D1(2018) (26th October 2017) - Han, Heonjong; Cho, Jae-Won; Lee, Sangyoung; Yun, Ayoung; Kim, Hyojin; Bae, Dasom; Yang, Sunmo; Kim, Chan Yeong; Lee, Muyoung; Kim, Eunbeen; Lee, Sungho; Kang, Byunghee; et al.
Abstract: Transcription factors (TFs) are major trans -acting factors in transcriptional regulation. Therefore, elucidating TF–target interactions is a key step toward understanding the regulatory circuitry underlying complex traits such as human diseases. We previously published a reference TF–target interaction database for humans—TRRUST (Transcriptional Regulatory Relationships Unraveled by Sentence-based Text mining)—which was constructed using sentence-based text mining, followed by manual curation. Here, we present TRRUST v2 (www.grnpedia.org/trrust ) with a significant improvement from the previous version, including a significantly increased size of the database consisting of 8444 regulatory interactions for 800 TFs in humans. More importantly, TRRUST v2 also contains a database for TF–target interactions in mice, including 6552 TF–target interactions for 828 mouse TFs. TRRUST v2 is also substantially more comprehensive and less biased than other TF–target interaction databases. We also improved the web interface, which now enables prioritization of key TFs for a physiological condition depicted by a set of user-input transcriptional responsive genes. With the significant expansion in the database size and inclusion of the new web tool for TF prioritization, we believe that TRRUST v2 will be a versatile database for the study of the transcriptional regulation involved in human diseases.